Pandangan Hukum Islam tentang Kewarisan Anak dalam Kandungan - Aswar Arifin; Ahmad Nuh (Al-Azhar Islamic Law Review, 2021)
This study aims to determine the views of Islamic law on the inheritance of children in the womb. This research is a descriptive qualitative research with data collected from various literature sources with a juridical normative approach. The results show that the position of the child in the womb with respect to inheritance in Islamic law is largely determined by two conditions that must be met, namely that he must be proven alive when the person who gave the inheritance dies, by paying attention to the minimum and maximum limits of the content. The second condition is that the child in the womb should be born alive at least a few minutes after birth marked by screams and movements. While the distribution of inheritance for children in the womb based on Islamic law, can be done in two ways, namely waiting until the birth of the baby is real or distributing the inheritance without waiting for the birth of the baby, by suspending the most part for the fetus if he is included in one of the an heir.